2008
DOI: 10.1177/031289620803300208
|View full text |Cite
|
Sign up to set email alerts
|

Does Disclosure Quality via Investor Relations Affect Information Asymmetry?

Abstract: High disclosure quality can be achieved through an effective investor-relations program and results in firm benefits such as enhanced market exposure, increased analyst coverage and institutional following. We examine the association between disclosure quality and information asymmetry where a checklist was used to evaluate a firm's Internet-based investor-relations practices. Firms with higher disclosure quality through their investor-relations activities have higher analyst following, more institutional shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 37 publications
(79 reference statements)
4
53
1
5
Order By: Relevance
“…These correlations are all, as expected, and are consistent with the results of former studies that have used these company characteristics to confirm the validity of their measurement instruments (as used to measure website contents - Chang et al, 2008;Orens et al, 2010;Trabelsi et al, 2008;Froidevaux, 2004).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…These correlations are all, as expected, and are consistent with the results of former studies that have used these company characteristics to confirm the validity of their measurement instruments (as used to measure website contents - Chang et al, 2008;Orens et al, 2010;Trabelsi et al, 2008;Froidevaux, 2004).…”
supporting
confidence: 90%
“…Regarding studies that assigned weights to individual attributes, it is further possible to distinguish between the assignment of weights to reflect the degree of detail 8 Cormier, Ledoux & Magnan, 2009;Orens et al, 2010Orens et al, : 1066 and to reflect the perceived importance thereof for users (Larrán & Giner, 2002: 75;Chang et al, 2008;Lai, Lin, Li & Wu, 2010).…”
Section: The Use Of Weightsmentioning
confidence: 99%
“…Specifi cally regarding the use of websites for IR, Chang et al (2008) found that Australian companies with websites having more information available showed greater analyst coverage, higher proportions of institutional investors, market capitalization, and trading volume. Chang, Hooi e Wee (2014) have shown the importance of active communication with analysts, especially in times of uncertainty, fi nding that disclosure by Australian companies on the internet correlate positively with accuracy of analysts' forecasts, in a scenario dominated by small companies with limited analyst coverage.…”
Section: Investor Relationsmentioning
confidence: 99%
“…So, the motivation of this study lies on the fact that IR activities are capable of aff ecting information asymmetry, changing the behavior of uninformed investors (Chang, D'anna, Watson & Wee, 2008). In this context, facilitating access to company information reduces the risk of private information trading, attracting investors and increasing the amount of stocks traded (Brown & Hillegeist, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although there exists a substantial amount of research measuring the use of corporate websites as communication channel, both in South Africa (Barac 2004;Esterhuyse & Wingard 2016;Loxton 2003;Nel & Baard 2006;Venter 2002) and internationally (Aerts, Cormier & Magnan 2007;Chang et al 2008;Froidevaux 2004;Gajewski & Li 2015;Orens et al 2010;Trabelsi, Labelle & Dumontier 2008), the measurement instruments used by such studies are often criticised (as discussed in the literature review) and few of these studies explicitly measured investor relations.…”
Section: Introductionmentioning
confidence: 99%